Rancang Bangun Mesin Pengurai Sabut Kelapa Menggunakan Dua Rol Pisau Pengurai - Arti Aulia Sari; Muh Miftahul Khair; Muh. Setiawan Sukardin; Zuingli Santo Bandaso (Journal of Energy, Materials, & Manufacturing Technology, 2023)
Rapid technological developments have led to the creation of various products in the industrial sector such as Polyester Composite Materials made from fiber and coconut coir powder. Decomposition of coconut husk takes a long time if conventionally, it requires an efficient machine and with better quality of decomposition results and machine construction. This study aims to design and test the effectiveness of the results of the design of the coconut coir decomposing machine. The research methods used are qualitative, quantitative and experimental. The design of the coconut coir decomposing machine uses a design power of 0.035Kw so that the author uses a 1Hp electric motor drive. The parsing knife consists of 2 cylindrical rollers with 143 pointed bolts attached to each side. Based on the test results on a qualitative approach, parallel blades are better because they produce more cocopeat, finely and neatly decomposed cocobristle and less cocofiber. The results of the test using a quantitative approach, the zigzag shape of the blade produces cocopeat with a percentage of 30.4% and a production capacity of 0.77kg/hour, cocobristle with a percentage of 29.9% and a production capacity of 0.75kg/hour, cocofiber with a percentage of 0.75kg/hour. 39.7% and the production capacity is 1kg/hour. Parallel blades produce cocopeat with a percentage of 31.6% and a production capacity of 0.85kg/hour, cocobristle with a percentage of 31.4% and a production capacity of 0.846kg/hour, cocofiber with a percentage of 37% and a production capacity of 0.997kg/hour.